(untitled) (Communicate: Journal of Library and Information Science, 2023)
The current volume has 19 articles, the first paper is titled: Staff Training as Determinant of Job Performance of Librarians in Public Universities in Southern Nigeria. Staff training was found to be an antidote to good job performance by the librarians. Second paper is: Records Management and Job Performance of Non-Academic Staff of Osun State Tertiary Institutions. The call is for management of tertiary institutions to invest in modern office equipments which assist in records management and in turn influence increased job performance. Information Literacy Skills as Factors Influencing Library Service Delivery in Public Universities in South West Nigeria is the third paper. The conclusion of the study is that information literacy skills are crucial skills for enhancing library service delivery. The fourth paper is; Social Media Use By ‘Infopreneurs’ during The Covid-19 Pandemic In Osun, State Nigeria. In view of the fact that ‘infopreneurs’ did not possess adequate knowledge of the dynamics of social media, it was recommended that they should transcend beyond personal development in acquiring the knowledge and exploit training avenues.